An Immunomodulatory Device Improves Insulin Resistance in Obese Porcine Model of Metabolic Syndrome - Angela J. Westover; Kimberly A. Johnston; Deborah A. Buffington; H. David Humes (Journal of Diabetes Research)
Obesity is associated with tissue inflammation which is a crucial etiology of insulin resistance. This inflammation centers around circulating monocytes which form proinflammatory adipose tissue macrophages (ATM). Specific approaches targeting monocytes/ATM may improve insulin resistance without the adverse side effects of generalized immunosuppression. In this regard, a biomimetic membrane leukocyte processing device, called the selective cytopheretic device (SCD), was evaluated in an Ossabaw miniature swine model of insulin resistance with metabolic syndrome. Treatment with the SCD in this porcine model demonstrated a decline in circulating neutrophil activation parameters and monocyte counts. These changes were associated with improvements in insulin resistance as determined with intravenous glucose tolerance testing. These improvements were also reflected in lowering of homeostatic model assessment- (HOMA-) insulin resistant (IR) scores for up to 2 weeks after SCD therapy. These results allow for the planning of first-in-man studies in obese type 2 diabetic patients.